Dihalohydration of Alkynols: A Versatile Approach to Diverse Halogenated Molecules. Issue 29 (18th July 2018) - Gibson, Samantha M.; D'Oyley, Jarryl M.; Higham, Joe I.; Sanders, Kate; Laserna, Victor; Aliev, Abil E.; Sheppard, Tom D.
Abstract : In this paper we outline how dihalohydration reactions of propargylic alcohols can be used to access a wide variety of useful halogenated building blocks. A novel procedure for dibromohydration of alkynes has been developed, and a selection of dichloro and dibromo diols and cyclic ethers were synthesized. The dihalohydration of homo‐propargylic alcohols provides a useful route to 3‐halofurans, which were shown to readily undergo cycloaddition reactions under mild conditions. Finally, a novel ring expansion of propargylic alcohols containing a cyclopropylalkyne provides access to halogenated alkenylcyclobutanes. Abstract : A novel procedure for the regioselective dibromination of alkynols to give dibromohydroxyketones is described. The application of dihalohydroxyketones in the synthesis of a variety of structurally novel brominated and chlorinated molecules is demonstrated.